Exploração da superfície catalítica de cobre monossubstituída para a adsorção do ácido fórmico - Alice Teixeira Silva (2023)
Climate change turns us into searching for sustainable energy sources. One such sources which may be a part of future’s power matrix is hydrogen gas. Hydrogen gas has significant energy density and it cleanly burns, and also it can be made sustainably. It should be stated, though the challenges of hydrogen gas as a fuel source, such as its hard and risky storage. A way to remedy such challenges may be in hydrogen carriers such as formic acid. Formic acid is an abundant molecule in many industrial parks, being subproducts of a lot of processes, and also it can be dehydrogenated cleanly and can be regenerated with CO2. The dehydrogenation reaction of formic acid may be catalyzed and selected through heterogeneous catalysis, specifically, adsorption on a copper surface. Studies on this catalytic surface show that its effectiveness can be heightened by including some more noble elements on the copper surface, such as platinum and palladium. The dehydrogenation reaction was already shown to be possible at temperatures close to ambient temperature using such catalytic surfaces. It can be cited that a development on such substituted surfaces comes in the form of monosubstitution of said noble elements on it, as it has been shown to increase its activity. This work explores such possibilities and simulates the adsorption of formic acid on monosubstituted surfaces as in to elucidate about the viability of the dehydrogenation reaction on such conditions, expanding on works already done on the field.